2019
DOI: 10.1103/physrevmaterials.3.013001
|View full text |Cite
|
Sign up to set email alerts
|

Topological Hall effect in thin films of Mn1.5PtSn

Abstract: Spin chirality in metallic materials with noncoplanar magnetic order can give rise to a Berry phase induced topological Hall effect. Here, we report the observation of a large topological Hall effect in high-quality films of Mn 1.5 PtSn that were grown by means of magnetron sputtering on MgO(001). The topological Hall resistivity is present up to μ 0 H ≈ 4 T below the spin reorientation transition temperature, T s = 185 K. We find that the maximum topological Hall resistivity is of comparable magnitude as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 35 publications
2
55
0
Order By: Relevance
“…In addition, microstructural defects like twins and grain boundaries of the polycrystalline samples may also act as pinning centers to stabilize the aSKs. Previous reports on analogous Heusler compounds, e.g., bulk Mn 2 PtSn [44] and thin films of Mn 2 PtSn [45], Mn 2−x PtSn [46], and Mn 2 RhSn [47] also revealed a THE but did not show an inverse hysteresis in the ρ yx loop. In Fig.…”
Section: Topological Hall Effectmentioning
confidence: 70%
“…In addition, microstructural defects like twins and grain boundaries of the polycrystalline samples may also act as pinning centers to stabilize the aSKs. Previous reports on analogous Heusler compounds, e.g., bulk Mn 2 PtSn [44] and thin films of Mn 2 PtSn [45], Mn 2−x PtSn [46], and Mn 2 RhSn [47] also revealed a THE but did not show an inverse hysteresis in the ρ yx loop. In Fig.…”
Section: Topological Hall Effectmentioning
confidence: 70%
“…This spin chirality generates an effective electromagnetic field for electrons through the spin Berry phase mechanism. The resulting Hall effect, known as the Topological Hall (TH) effect, has been observed in perovskite oxides [9][10][11][12], chiral magnets [13,14], frustrated magnets [15], and Heusler alloys [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic properties in spin glasses revealed that chiral magnetic interactions between neighboring spins can also play a key role in metallic systems. The RKKY model was extended to 3-sites to the bilayer systems has been predicted by [18] that a large Dzyaloshinskii-Moriya interaction (DMI) with magnetic film and a heavy material with large spin-orbit coupling. The best solution up to now seems to increase the effective magnetic volume by using multilayer stacks composed of multiple repetitions of thin magnetic metal layers separated by heavy metal nonmagnetic layers grown by sputtering deposition.…”
Section: Multilayer Thin Filmsmentioning
confidence: 99%